ASSURED FOOD SECURITY THROUGH SUGARCANE-POTATO INTERCROPPING IN INDIA - Nankar, J. T. (Potato Journal, 2013)
Intercropping of two or more crops is an old practice in India, especially under rainfed conditions. The system helps to improve utilization of natural resources, i.e. sunlight, land and water, and to combine cultural practices, often resulting increased productivity per unit area and time. With the limits on the availability of arable land and rapid increase in the population, intercropping needs to be adopted by farming systems in developing countries for producing more food and other agricultural commodities from the same available area.